Auroral and Non‐Auroral H3+ Ion Winds at Uranus With Keck‐NIRSPEC and IRTF‐iSHELL - Emma M. Thomas; Tom S. Stallard; Henrik Melin; Mohammad N. Chowdhury; Luke Moore; James O’Donoghue; Rosie E. Johnson; Ruoyan Wang; Katie L. Knowles; Paola I. Tiranti; Neil Dello Russo; Ron J. Vervack Jr.; et al. (Geophysical Research Letters)
Abstract To date, no investigation has documented ionospheric flows at Uranus. Previous investigations of Jupiter and Saturn have demonstrated that mapping ion winds can be used to understand ionospheric currents and how these connect to magnetosphere‐ionosphere coupling. We present a study of Uranus's near infrared emissions (NIR) using data from the Keck II Telescope's Near InfraRed SPECtrograph (NIRSPEC) and the InfraRed Telescope Facility's iSHELL spectrograph. H3+ emission lines were used to derive dawn‐to‐dusk intensity, ionospheric temperatures and ion densities to identify auroral emissions, with their Doppler shifts used to measure ion velocities. We confirm the presence of the southern NIR aurora in 2016, driven by elevated H3+ column densities up to 6.0 × 1016 m−2. While no auroral emissions were detected in 2014, we find a 14%–20% super rotation across the planet's disk in 2014 and a 7%–18% super rotation in 2016.